Probiotic as Adjuvant Significantly Improves Protection of the Lanzhou Trivalent Rotavirus Vaccine against Heterologous Challenge in a Gnotobiotic Pig Model of Human Rotavirus Infection and Disease - Parreño, Gladys Viviana (2022)
This preclinical study in the gnotobiotic (Gn) pig model of human rotavirus (HRV) infection and disease evaluates the effect of probiotic Lactobacillus rhamnosus GG (LGG) as a mucosal adjuvant on the immunogenicity and cross-protective efficacy of the Lanzhou live oral trivalent (G2, G3, G4) vaccine (TLV, aka LLR3). Gn pigs were immunized with three doses of TLV with or without concurrent administration of nine doses of LGG around the time of the first dose of the TLV vaccination, and were challenged orally with the virulent heterotypic Wa G1P[8] HRV. Three doses of TLV were highly immunogenic and conferred partial protection against the heterotypic HRV infection. LGG significantly enhanced the intestinal and systemic immune responses and improved the effectiveness of protection against the heterotypic HRV challenge-induced diarrhea and virus shedding. In conclusion, we demonstrated the immune-stimulating effects of probiotic LGG as a vaccine adjuvant and generated detailed knowledge regarding the cross-reactive and type-specific antibody and effector B and T cell immune responses induced by the TLV. Due to the low cost, ease of distribution and administration, and favorable safety profiles, LGG as an adjuvant has the potential to play a critical role in improving rotavirus vaccine efficacy and making the vaccines more cost-effective.